Adherence to geriatric assessment-based recommendations in older patients with cancer: a multicenter prospective cohort study in Belgium. (14th June 2018) - Kenis, C; Decoster, L; Flamaing, J; Debruyne, P R; De Groof, I; Focan, C; Cornélis, F; Verschaeve, V; Bachmann, C; Bron, D; Luce, S; Debugne, G; et al.
Abstract: Background: In the general older population, geriatric assessment (GA)-guided treatment plans can improve overall survival, quality of life and functional status (FS). In GA-related research in geriatric oncology, studies mainly focused on geriatric screening and GA but not on geriatric recommendations, interventions and follow-up. The aim of this study was to investigate the adherence to geriatric recommendations and subsequent actions undertaken in older patients with cancer. Patient and methods: A prospective Belgian multicenter ( N = 22) cohort study included patients ≥70 years with a malignant tumor upon oncologic treatment decision. Patients with an abnormal result on the geriatric screening (G8 ≤14/17) underwent GA. Geriatric recommendations were formulated based on GA results. At follow-up the adherence to geriatric recommendations was documented including a description of actions undertaken. Results: From November 2012 till February 2015, G8 screening was carried out in 8451 patients, of which 5838 patients had an abnormal result. Geriatric recommendations data were available for 5631 patients. Geriatric recommendations were made for 4459 patients. Geriatric interventions data were available for 4167 patients. A total of 12 384 geriatric recommendations were made. At least one different geriatric recommendation was implemented in 2874 patients. A dietician, social worker and geriatrician intervened most frequently for problems detected on the nutritional, social and functional domain. A total of 7569 actions were undertaken for a total of 5725 geriatric interventions, most frequently nutritional support and supplements, extended home care and psychological support. Conclusions: This large-scale Belgian study focuses on the adherence to geriatric recommendations and subsequent actions undertaken and contributes to the optimal management of older patients with cancer. We identified the domains for which geriatric recommendations are most frequently made and adhered to, and which referrals to other health care workers and facilities are frequently applied in the multidisciplinary approach of older patients with cancer.